1999
DOI: 10.1046/j.1365-2958.1999.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple transcription factors of the FNR family in denitrifying Pseudomonas stutzeri: characterization of four fnr‐like genes, regulatory responses and cognate metabolic processes

Abstract: Fig. 2. Alignment of the deduced amino acid sequences of the fnr homologues from P. stutzeri and fnr from E. coli. The DnrE product is derived from the second potential start site of translation (see Fig. 5). The alignment was performed with the CLUSTAL 4 programme of the DNASIS 2.5 software. The helix±turn±helix region (HTH) is overlined; the dashed line indicates the dimerization domain; the triangle points to the critical position for dimer stabilization. B, cysteine residues for [4Fe±4S] cluster ligation; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 0 publications
1
49
0
Order By: Relevance
“…Northern blot analysis of the nirSTM operon of Ps. stutzeri (ZoBell) showed that two transcripts originated from the nirS promoter, one containing nirS alone, the other nirS, T and M (Ha$ rtig & Zumft, 1999). In neither pseudomonad is the nirS gene followed by a terminator such as that identified in Pa. pantotrophus (Fig.…”
Section: Northern Blot Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Northern blot analysis of the nirSTM operon of Ps. stutzeri (ZoBell) showed that two transcripts originated from the nirS promoter, one containing nirS alone, the other nirS, T and M (Ha$ rtig & Zumft, 1999). In neither pseudomonad is the nirS gene followed by a terminator such as that identified in Pa. pantotrophus (Fig.…”
Section: Northern Blot Studiesmentioning
confidence: 99%
“…aeruginosa (Arai et al, 1997 ;Hasegawa et al, 1998) and the set of regulatory proteins named DnrE, DnrS and DnrD in Ps. stutzeri (Vollack et al, 1999). All these proteins bear a high similarity to the transcriptional activator Fnr of Escherichia coli, but lack the N-terminal cysteines which allow the formation of an oxygen-labile iron-sulphur cluster in Fnr (Khoroshilova et al, 1995 (Zumft, 1997 ;Baker et al, 1998), but the environmental signals which trigger denitrification are different as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We set the pH of the culture medium to 7.5 or 6.5 and grew completely consuming cells (strain A1601) alone in the presence or absence of 10 mM of exogenous nitrite. We incubated the cells under fully aerobic conditions because oxygen represses nitrite reductase activity (Vollack et al, 1999), thus preventing nitrite reduction-and consequently detoxification-during the experiment. We measured cell density over time (measured as OD 600 ; Figures 4a and b) and quantified the maximum specific growth rate (u max (min − 1 )) for each culture (Figure 4c).…”
Section: Alternative Explanations For the Accumulation Of Nitritementioning
confidence: 99%
“…Crp/Fnr regulators are generally classified into different subfamilies (e.g., CooA, Crp, Dnr, FixK, Fnr, HbaR, NnrR, etc.) according to phylogenetic affiliations (50). The increasing number of sequenced whole genomes has added to a growing list of Crp/Fnr family regulators identified in bacteria (9,26); however, functions for most are not well defined.…”
mentioning
confidence: 99%